If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4v + 2 = 2(v + 7) Reorder the terms: 2 + -4v = 2(v + 7) Reorder the terms: 2 + -4v = 2(7 + v) 2 + -4v = (7 * 2 + v * 2) 2 + -4v = (14 + 2v) Solving 2 + -4v = 14 + 2v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-2v' to each side of the equation. 2 + -4v + -2v = 14 + 2v + -2v Combine like terms: -4v + -2v = -6v 2 + -6v = 14 + 2v + -2v Combine like terms: 2v + -2v = 0 2 + -6v = 14 + 0 2 + -6v = 14 Add '-2' to each side of the equation. 2 + -2 + -6v = 14 + -2 Combine like terms: 2 + -2 = 0 0 + -6v = 14 + -2 -6v = 14 + -2 Combine like terms: 14 + -2 = 12 -6v = 12 Divide each side by '-6'. v = -2 Simplifying v = -2
| -8=2(x+6) | | 5x+3y=371 | | w+10=3w-10 | | 4(-5+7a)=26+5a | | 9/28•19/54 | | (14n/3)=8(n-14) | | -25/28•(-21) | | 2X-(5X+9)=8-3X | | 1+6(x-4)=2-8(x-9) | | (x-6)/4=20 | | 4(4+4k)=-32+8k | | -297=4+7(-5v-8) | | 10+2-21=0 | | x-6/4=20 | | ((T^2+3t-8)-(t^2-2t+6))(t-4)=0 | | 7+20x+12x= | | 3-9t=-10t | | 4X+48=8(X+6)-4X | | 252=4(-1-8v) | | -3-8p=-9p+6 | | 3a+3=9+a | | 4x-3(4-3x)=5(x-4)-40 | | Y/3=40 | | 17/6=34/x | | 2+3(x+5)=38 | | 154=7(7k+1) | | -4(n-6)=n+6 | | 5+8(x-3)=4-4(x-3) | | 4(3Z-1)-5(Z+4)=5(Z+1) | | 2/3=1/9(27) | | -27a-42=a+98 | | T/0.16=0.5/0.4 |